(untitled) - Jolly, William L (New York, 1991)
The book describes and explains the intellectual tools used in the systematization of inorganic chemistry. It assumes simple bonding theory with the rudiments of thermodynamics, kinetics, atomic and molecular orbital theory, orbital hybridization, the electronegativity concept
Keywords: Hóa học, vô cơ,Chemistry, inorganic